(untitled) (Economic studies journal, 2023)
By using exploratory and confirmatory factor analysis, the main aim of the current study is to reveal the essential dimensions of communication methods of receptionists that play the vital role in the retention of customers in private hospitals in Libya. A quantitative method was conducted, and (Google Forms Questionnaire) was used. Convenience sampling approach was used. Number of (83) Questionnaires were utilized for analysis. For data preparation and data analysis, three programs were utilized: Excel, SPSS, and Google Spread Sheet. Principal Components Analysis with Varimax methods were used for exploratory analysis and several fit model’s indicators for confirmatory were also used. The result of the study extracted three dimensions of communication methods of receptionists named: ethics dimension; responsiveness & organization dimension, and technology & humanly dimension. These findings carry important implications for the theoretical understanding of the customer retention and should be careful by hospitals that intention to predict and affect customer retention. Finally, further research and recommendations were stated.